Humorous Reader’s Comments to a Post on Facebook Page About the Accurate Way to Measure Body Temperature in the Effort to Curb COVID-19 Transmission - Ahmad Zaimi, Rasyqah Ifah; Ramli, Salfarina (International Journal of Human and Health Sciences (IJHHS), 2022)
Objectives: Humour can be identified as parody, teasing, pun, and sarcasm. Evidence shows that humour fosters interactions, keeps the conversation moving and contributes to effective message delivery. In this study, the engagement of social media users with health educational posts was explored by assessing the reader’s humorous comments. Method: Fever is one of the common symptoms of COVID-19. A post published by the Public Health Malaysia Facebook page addressed the concern over the adverse effects of infrared thermometer on the brain. The post also gave additional information with no pun intended by mentioning that the rectal temperature is the most accurate way to measure body temperature, but such screening method is impossible and impractical in public places. This study selected the post and analysed 346 comments under the post. Thematic content analysis was carried out to examine the emerging humorous theme. Results. 60 comments were coded as humorous comments. The themes identified include additional information about rectal measurement is funny (14%), while jokes about rectum consisted of teasing, innuendo (54%), laugh emoji and haha comment (30%). From the results, the no pun intended additional statement about the rectal temperature in the Facebook post has sparked humorous comments from the netizens. Conclusion. This study indicated humorous utterances and exchanges comments about the Facebook post contributed to positive health education impact by indirectly informing netizens the accurate way to measure body temperature. This is an essential piece of information in the pandemic era where everybody's contribution to curb COVID-19 transmission is important. International Journal of Human and Health Sciences Supplementary Issue: 2022 Page: S35